P73 Evaluation of patient experience and outcomes in a virtual nodule clinic. (December 2018) - Morton, A; Rowe, S; Smith, K; Beckett, P
Abstract : Background: Following the publication of BTS guidelines on management of pulmonary nodules, we introduced a 'virtual nodule clinic' to implement best practice risk assessment and management, standardise practice, and reduce the number of physical out-patient appointments through a service predominantly delivered by a LCNS through telephone consultations. We aimed to assess the experience and outcomes for patients in our new service. Methods: We extracted information on cases referred between December 2016 and March 2018, from the Access database that is used to record information during our nodule MDT. The database includes patient demographics and the data items needed to calculate an initial Brock score on individual nodules and was supplemented with information from the electronic patient record where necessary. We also carried out a postal survey of 30 patients. Results: 320 patients were identified, with median age 70 years and 52% were male. Median nodule size was 7 mm (IQR 6–10). 30% of the patients have been discharged and 61% remain under surveillance. 28 patients (9% of total) required further evaluation for suspected lung cancer, of which 17 (5%) were ultimately diagnosed with lung cancer. Final stage distribution (mostly clinical) was stage I (12), stage II (2), stage III (2), stage IV (1). Of the 17 lung cancers, only 5 underwent curative treatment (3 SABR, 2 lobectomy), with other patients being considered unsuitable for any treatment, or opting for further surveillance/discharge. Patient satisfaction with all aspects of the service was high. Conclusions: Around 5% of our patients are eventually diagnosed with lung cancer which is similar to previous studies of incidental nodules, but less than a third of these underwent any treatment. Pathways to screen out patients who will not benefit from treatment if cancer is later diagnosed would help to minimise the resource impact of nodule management but is very difficult in a virtual clinic. Patients value the nurse-led model of telephone consultation very highly and there is scope to extend this in other areas of lung cancer care.